Peranan Guru BK dalam Manajemen Waktu Belajar Siswa SMP Negeri 1 Aek Ledong pada Masa Pandemi Covid-19 - Ziah Lestari Sembiring; Fany Chairunnisa (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2022)
This research to reveal how the BK teacher's role in managing student studies time at SMP Negeri 1 Aek Ledong during the Covid-19 pandemic. From the data collected, it was obtained information that during the Covid-19 pandemic, it was difficult for students to manage study time, both at school and at home. Many schools were also closed due to the impact of this pandemic, so students experienced delays in providing learning materials at school. The method used in this research is a qualitative method with a descriptive approach, data collection techniques are carried out through interview guidelines, observation guidelines, and distributing questionnaires. The subjects of the research were headmaster, the BK teacher and 35 students in grade IX. The results of this study showed that the role of guidance and counseling teachers in managing student study time at SMP Negeri 1 Aek Ledong during the Covid-19 pandemic was in good condition.